Diagnosing Carotid Near-Occlusion with Phase-Contrast MRI - Johansson, E.; Zarrinkoob, L.; Wåhlin, A.; Eklund, A.; Malm, J. (American Journal of Neuroradiology, 2021)
SUMMARY: Carotid near-occlusion is a frequently overlooked diagnosis when CTA examinations are assessed in routine practice. To evaluate the potential value of phase-contrast MR imaging in identifying near-occlusion, we examined 9 carotid near-occlusions and 20 cases of conventional ≥50% carotid stenosis (mean stenosis degree, 65%) with phase-contrast MR imaging. Mean ICA flow was lower in near-occlusions (52 mL/min) than in conventional ≥50% stenosis (198 mL/min, P < .001). ICA flow of ≤110 mL/min was 100% sensitive and specific for near-occlusion. Phase-contrast MR imaging is a promising tool for diagnosing carotid near-occlusion.PCphase-contrast